2012
DOI: 10.1038/onc.2012.359
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS9 is a functional tumor suppressor through inhibiting AKT/mTOR pathway and associated with poor survival in gastric cancer

Abstract: Using genome-wide promoter methylation analysis, we identified a disintegrin-like and metalloprotease with thrombospondin type 1 motif 9 (ADAMTS9) is methylated in cancer. We aim to clarify its epigenetic inactivation, biological function and clinical implication in gastric cancer. ADAMTS9 was silenced in 6 out of 8 gastric cancer cell lines. The loss of ADAMTS9 expression was regulated by promoter hypermethylation and could be restored by demethylation agent. Ectopic expression of ADAMTS9 in gastric cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
87
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 33 publications
8
87
0
1
Order By: Relevance
“…ADAMTS9 has been found to be a critical tumor suppressor of gastric cancer progression through suppression of oncogenic AKT/mTOR signaling. 51 In accordance with our findings, ectopic expression of ADAMTS9 in gastric cancer cell lines (AGS, BGC823) was found to induce apoptosis. The mechanism of the action of ADAMTS is required to be understood more comprehensively.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…ADAMTS9 has been found to be a critical tumor suppressor of gastric cancer progression through suppression of oncogenic AKT/mTOR signaling. 51 In accordance with our findings, ectopic expression of ADAMTS9 in gastric cancer cell lines (AGS, BGC823) was found to induce apoptosis. The mechanism of the action of ADAMTS is required to be understood more comprehensively.…”
supporting
confidence: 75%
“…Therefore, we can suggest that H 2 O 2 may trigger oxidative damage and ADAMTSinduced apoptosis in chondrocytes (Figure 8). 51 Our findings demonstrated that the applied concentration of H 2 O 2 caused cellular damage in OUMS-27 cells in two hours. Additionally, HPL was observed to protect OUMS-27 against oxidative damage, inhibit the damage of ECM by decreasing ADAMTS5 level, and protect cartilage tissue from the secondary damage upon abnormal and pathological cell death at a dose of 400 μg/ml.…”
mentioning
confidence: 76%
“…For example, antiangiogenic genes included septin 9 (SEPT9) and protein tyrosine phosphatase, nonreceptor type 23 (PTPN23), which inhibit EC proliferation and migration, respectively (28,30). The antitumorigenic genes included ADAMTS9, which blocks tumor growth by inhibition of Akt activation (25); DYRK1A, which inhibits the growth of AML cells (26), and CAMK2N1, which inhibits prostate cancer progression through androgen receptor-dependent signaling (27). These activities were in line with the originating tumors, suggesting that TECs derived from CRC with a Th1-TME express a set of "memory genes."…”
Section: Discussionmentioning
confidence: 99%
“…The ADAMTS9‐AS2 antisense transcript of ADAMTS9 gene was shown to be significantly down‐regulated in glioma tissues and was negatively correlated with tumour grade and prognosis. The ADAMTS9 gene is widely expressed in foetal and adult tissues, functioning as a tumour suppressor gene in diverse cancer types 75. Overexpression of ADAMTS9‐S2 in glioma cells inhibited cell migration and invasion, while ADAMTS9‐S2 silencing increased the malignancy of GBM cells, validating its tumour suppressor activity 76…”
Section: Tumour‐suppressor Lncrnasmentioning
confidence: 99%